Basal forebrain GABAergic innervation of olfactory bulb periglomerular interneurons - Sanz Diez, Alvaro (J Physiol, 2019)
KEY POINTS: Basal forebrain long‐range projections to the olfactory bulb are important for olfactory sensitivity and odour discrimination. Using optogenetics, it was confirmed that basal forebrain afferents mediate IPSCs on granule and deep short axon cells. It was also shown that they selectively innervate specific subtypes of periglomerular (PG) cells. Three different subtypes of type 2 PG cells receive GABAergic IPSCs from the basal forebrain but not from other PG cells. Type 1 PG cells, in contrast, do not receive inputs from the basal forebrain but do receive inhibition from other PG cells. These results shed new light on the complexity and specificity of glomerular inhibitory circuits, as well as on their modulation by the basal forebrain. ABSTRACT: Olfactory bulb circuits are dominated by multiple inhibitory pathways that finely tune the activity of mitral and tufted cells, the principal neurons, and regulate odour discrimination. Granule cells mediate interglomerular lateral inhibition between mitral and tufted cells’ lateral dendrites whereas diverse subtypes of periglomerular (PG) cells mediate intraglomerular lateral inhibition between their apical dendrites. Deep short axon cells form broad intrabulbar inhibitory circuits that regulate both populations of interneurons. Little is known about the extrabulbar GABAergic circuits that control the activity of these various interneurons. We examined this question using patch‐clamp recordings and optogenetics in olfactory bulb slices from transgenic mice. We showed that axonal projections emanating from diverse basal forebrain GABAergic neurons densely project in all layers of the olfactory bulb. These long‐range GABAergic projections provide a prominent synaptic input on granule and short axon cells in deep layers as well as on selective subtypes of PG cells. Specifically, three different subclasses of type 2 PG cells receive robust and target‐specific basal forebrain inputs but have little local interactions with other PG cells. In contrast, type 1 PG cells are not innervated by basal forebrain fibres but do interact with other PG cells. Thus, attention‐regulated basal forebrain inputs regulate inhibition in all layers of the olfactory bulb with a previously overlooked synaptic complexity that further defines interneuron subclasses.